Effect of Trust and Satisfaction on Outpatient Loyalty at Sundari Hospital in 2025 - Muhammad Adiul Ilham; Ribka Panjaitan; Julita Arnis; Dermawan Syah Putra Gulo (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2026)
Service quality is a critical determinant of patient satisfaction and loyalty in healthcare settings, as it reflects the extent to which services meet patient expectations. This study aimed to examine the effects of trust and patient satisfaction on outpatient loyalty at Sundari Hospital in 2025. A quantitative descriptive approach was employed, involving 99 outpatient respondents who completed structured questionnaires. Data were analyzed using univariate and bivariate techniques, with the chi-square test applied to assess the associations between variables. The results indicated that 63.6% of respondents reported high levels of trust, 60.6% reported high satisfaction, and 56.6% demonstrated loyalty toward the hospital. Chi-square analysis revealed that both trust (p = 0.003) and satisfaction (p = 0.012) significantly influenced outpatient loyalty. The findings confirm that enhancing patient trust and satisfaction can strengthen loyalty, which is essential for sustaining patient engagement and promoting repeat visits. These results provide practical insights for healthcare managers seeking to improve service quality and patient-centered strategies, highlighting the importance of fostering trust and satisfaction to achieve better patient retention and long-term institutional performance.